Research on Rainfall Infiltration Characteristics of Loess Slopes Based on Different Rainfall Intensities - GUAN Xiaodi; YAO Yifan (Renmin Zhujiang)
In this paper,a homogeneous loess slope in Qingyang,Gansu Province is used as a reference prototype.An indoor model slope that satisfies similar conditions is built.Rainfall infiltration experiments are carried out on the slope under different rainfall intensities,and the corresponding rainfall infiltration rules and scour laws are obtained.The research results show that the rainfall infiltration rate is different at different positions of the slope,which is in descending order of the top,the foot,and the middle of the slope.The rainfall infiltration depth is the largest at the foot of the slope,followed by that at the top of the slope,and the smallest value is observed at the middle of the slope.The rainfall infiltration depth of the slope is 10~15 cm,15~25 cm,18~35 cm,and 20~40 cm in the cases of light rain,moderate rain,heavy rain,and rainstorm,respectively.